2005
DOI: 10.1007/s00449-005-0021-4
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimization in Aspergillus niger fermentation for selective product enhancement

Abstract: A multi-objective optimization formulation that reflects the multi-substrate optimization in a multi-product fermentation is proposed in this work. This formulation includes the application of e-constraint to generate the trade-off solution for the enhancement of one selective product in a multi-product fermentation, with simultaneous minimization of the other product within a threshold limit. The formulation has been applied to the fed-batch fermentation of Aspergillus niger that produces a number of enzymes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A protease isolated from B. licheniformis had a reduced rate of hydrolysis and enzyme selectivity with increased substrate concentration (Butré et al, 2014). On the contrary, protease from A. niger revealed that at least 30% of the activity could be increased if optimal conditions are provided (Mandal et al, 2005). These facts can lead to the different availability of products that do not affect the measurements of digestibility but may impact the microbial composition.…”
Section: Discussionmentioning
confidence: 99%
“…A protease isolated from B. licheniformis had a reduced rate of hydrolysis and enzyme selectivity with increased substrate concentration (Butré et al, 2014). On the contrary, protease from A. niger revealed that at least 30% of the activity could be increased if optimal conditions are provided (Mandal et al, 2005). These facts can lead to the different availability of products that do not affect the measurements of digestibility but may impact the microbial composition.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple and conflicting objectives appear often in the design and optimisation of dynamic bioprocesses (e.g., [12,23,24,33,39]). The resulting multi-objective optimisation problems yield a set of so-called Pareto optimal solutions instead of one single optimal solution in singleobjective optimisation problems [29].…”
Section: Introductionmentioning
confidence: 99%
“…The desirability function has been used for the multiresponse optimization of the production of enzymes, such as proteases and catalases [40] and cellulases [41] as well as for the application of enzymes, as reported by Castro et al [29] regarding the use of multienzyme complexes containing amylases and proteases for the hydrolysis of babassu case.…”
Section: Resultsmentioning
confidence: 99%